Pengembangan Media Pembelajaran Matca Terhadap Kemampuan Pemahaman Matematis Pada Materi Aljabar - Ovianti, Wida; Prihatin, Iwit; Abdillah, Abdillah (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to develop MATCA learning media for mathematical understanding abilities in algebra material that reaches levels of validity, practicality, and effectiveness. This research is included in development research with the ADDIE model. The instruments used in this research were expert validation sheets, questionnaires, and test questions. The subjects in this research were 24 students in class VII of SMP Negeri 19 Pontianak. Based on the results of the first research, the validation of MATCA learning media with an average score from the three experts was 81.78% in the very valid criteria with the very valid category. The second is practicality, judging from the questionnaire scores filled out by teachers and students, the percentage obtained was 85.41% with very practical criteria. Meanwhile, effectiveness can be seen from the results of the posttest results of students with a total of 18 students completing the test out of 24 students with a percentage of 75% and the average student score which is calculated using the average score formula and as a percentage of the overall student score so that A score of 77.96 was obtained based on the school's KKM score of 74, so the average student test results had complete criteria and were classified as effective. So that the MATCA learning media is suitable for use in mathematics learning in algebra material